FATIGUE LIFE ANALYSIS IN MECHANICAL STRUCTURE DUE TO RANDOM LOADING USING FREQUENCY DOMAIN ANALYSIS APPROACH - WIRADITA (NIM : 13106122); Pembimbing : Prof. Dr. Ir. Komang Bagiasna, DWI
A mechanical structure receiving the dynamic load might experience fatigue failure. However, its sign is quite difficult to be detected. Hence, fatigue life estimation as an alternative effort is proposed to avoid the impact of this failure. The aim of this research is to estimate fatigue life of mechanical structure which base is excited randomly with varying levels of RMS value. This base random excitation is generated by a shaking table on which the mechanical structure is installed, so that this setup can represent a fatigue failure of mechanical structure due to an excitation on its base. A finite element model have been developed to represent the structure, therefore, the whole process of fatigue life calculation can be done on this model, instead of having an fatigue experiment on the real structure. To ensure that the model is representative, two experiments have been conducted: FRF test to validate the natural frequency of model and power spectrum to validate the vibration response. The results of this research stated that this mechanical structure will experience fatigue failure at the location around welding joint. In addition it also obtained that the increase of vibration level will decrease fatigue life of mechanical structure exponentially.